Workshop Pemanfaatan Articulate Storyline Bagi Guru Untuk Mengembangkan Media Pembelajaran Berdiferensiasi - Fatma Wati; Ardo Okilanda; Firda Az Zahra; Azza Nuzullah Putri; Khairil Arif; Muhammad Fakhrur Rozi; Yogi Arnaldo; Harmedi Yulian Saputra (Universitas PGRI Palembang, 2024)
The Workshop on Using Articulate Storyline to develop learning media for Junior High School Teachers in Agam Regency aims to provide training for teachers so that they are able to develop their own learning media according to the characteristics of their students. This activity was successful in increasing teachers' conceptual understanding and practical skills in integrating learning technology. Post-workshop evaluation revealed significant improvements in teachers' conceptual understanding regarding the use of Articulate Storyline for online and/or digital learning at the Junior High School level. Participants gain in-depth insight into the user interface, key features, and potential applications. In addition, this workshop was effective in improving participants' practical skills, including designing interactive learning materials, selecting appropriate media, and integrating multimedia elements. The result is that teachers feel more confident and ready to face the challenges of online and/or digital learning and are able to create more dynamic learning. The transformation of the teaching paradigm is the main highlight, namely teachers experiencing a positive shift in their approach to technology in everyday teaching. This workshop not only provides technical expertise, but also creates the foundation for a mutually supportive and inspiring learning community in Agam Regency. Overall, this workshop succeeded in creating a positive and sustainable impact in improving the skills and learning approaches of junior high school teachers in Agam Regency.